ANALISIS DATA PENJUALAN POP ICE MENGGUNAKAN POWER BI - mawar dinata, ridho (PT. ZIVANA CENDEKIAWAN BANGSA, 2024)
Selling pop ice is an integrated activity to develop strategic plans aimed at satisfying the needs and desires of buyers/consumers, useful for generating profitable sales. The definition of sales is a transaction activity carried out by 2 (two) or more parties using legal payment instruments. The aim of sales is to make a profit from the products or services produced by the producer with good management and also expecting maximum profits. The research came directly to the MSME locations to conduct interviews and observations while taking several photos as data documentation to complete the report.